2022
DOI: 10.1038/s41598-022-10661-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drying methods on natural antioxidants, phenols and flavanones of immature dropped Citrus sinensis L. Osbeck fruits

Abstract: Citrus fruits are famous for nutritional value and studies are there for extraction of secondary metabolites from citrus waste. An attempt was made to quantify antioxidants, flavonoids and phenols from dropped fruits of 8–24 mm size, to find the impact of freeze and hot-air oven drying techniques on extraction. Flavonoids (hesperidin, narirutin/isonaringin, diosmin and didymin/neoponcirin) were quantified through high performance liquid chromatography (HPLC) and total phenols (TPC) were estimated by Folin-Cioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
4
16
0
Order By: Relevance
“…The high correlations between DPPH with didymin ( r = −0.529, p < 0.01) and between FRAP with 3,3′,4′,5,6,7-hexamethoxyflavone were found in the present study, suggesting these two compounds might be potent antioxidants in the orange peel. In line with our results, a high correlation between didymin and DPPH ( r = 0.83, p < 0.01) was found in a recent report studying immature dropped Citrus sinensis L. Osbeck fruits [ 31 ].…”
Section: Resultssupporting
confidence: 92%
“…The high correlations between DPPH with didymin ( r = −0.529, p < 0.01) and between FRAP with 3,3′,4′,5,6,7-hexamethoxyflavone were found in the present study, suggesting these two compounds might be potent antioxidants in the orange peel. In line with our results, a high correlation between didymin and DPPH ( r = 0.83, p < 0.01) was found in a recent report studying immature dropped Citrus sinensis L. Osbeck fruits [ 31 ].…”
Section: Resultssupporting
confidence: 92%
“…These are well known to be good for health and can be obtained through tea, vegetable, and fruit intake. In particular, phenolic and carotenoid compounds in leafy vegetables or fruits have excellent antioxidant properties in scavenging free radicals [ 2 , 3 , 4 ]. In this context, Mangifera indica L. (mango) has proven to be a good example.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies conducted on fruits of Citrus sinensis demonstrated that freeze drying technique expressed a higher content of phenol and also antioxidants. Flavonoids (hesperidin) were found to be decreased during heat drying (170). Due to the heat-sensitive nature of phenol compounds and the activation of polyphenol oxidase and peroxidase during the thermal drying process, phenolic compounds are destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, polyphenol oxidase enzyme activity was reduced in freeze drying, which was conducted at a lower temperature. So, instead of using a heat drying process, freeze drying is the best alternative for preserving and quality extraction of bioactive compounds (170). A study on the preservation of antioxidant capacity and health-promoting components in frozen baby mustard also found that blanching before freezing diminishes antioxidant capacity levels as well as the contents of highcontent glucosinolates and ascorbic acid (171).…”
Section: Discussionmentioning
confidence: 99%